Video Transmission over LTE-Unlicensed - Aseeri, Fatema Mahmood (2017)
A Master of Science thesis in Electrical Engineering by Fatema Mahmood Aseeri entitled, "Video Transmission over LTE-Unlicensed," submitted in November 2017. Thesis advisor is Dr. Mohamed Hassan and thesis co-advisor is Dr. Mahmoud H. Ismail. Soft and hard copy available.